Contamination in Pasir Gudang area, Peninsular Malaysia: what can we learn from Kim Kim River chemical waste contamination? - Yap, Chee Kong; Peng, Tony Shih Hao; Chee, Seng Leow (International Burch University, 2019)
This paper reviews monitoring studies of chemical pollutant in the Straits of Johore, especially in Pasir Gudang area. The Kim Kim River chemical waste pollution occurred in March 2019 is reviewed for comparison with the previously reported scientific data. It is concluded that reporting monitoring data in the scientific literature is just a knowledge sharing without any practical implications. Only heavy pollution cases involving human health implications would trigger governing bodies immediate actions. Therefore, reports of scientific monitoring data should be treated with high importance and governing bodies should be working closely with those researchers for the benefits of public at large. It is recommended that ‘Polluters Pay Principle’ should be fully adopted in line with stricter laws and regulations with effective management of clean river sustainability in Malaysia.